2020
DOI: 10.1038/s41598-020-70610-0
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase Cullin-1 associates with chromatin and regulates transcription of specific c-MYC target genes

Abstract: Transcription is regulated through a dynamic interplay of DNA-associated proteins, and the composition of gene-regulatory complexes is subject to continuous adjustments. Protein alterations include post-translational modifications and elimination of individual polypeptides. Spatially and temporally controlled protein removal is, therefore, essential for gene regulation and accounts for the short half-life of many transcription factors. The ubiquitin-proteasome system is responsible for siteand target-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…The nuclear UPS was found to regulate the turnover of many different components of transcriptional complexes [54]. Particular attention was paid to the role of cullin 1 (CUL1) and cullin 4B (CUL4B) [55]. On the other hand, it is known that in addition to the inhibitory effects of neddylation, MLN4924 also shows neddylation-independent activities.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear UPS was found to regulate the turnover of many different components of transcriptional complexes [54]. Particular attention was paid to the role of cullin 1 (CUL1) and cullin 4B (CUL4B) [55]. On the other hand, it is known that in addition to the inhibitory effects of neddylation, MLN4924 also shows neddylation-independent activities.…”
Section: Discussionmentioning
confidence: 99%
“…According to the GO analysis, Cullin protein was also involved in cell cycle progression, signal transduction and transcription, intracellular metabolism, and the corresponding response to stimuli. Yet, surprisingly, this protein has not been studied in parasites, we suggested that it could provide clues for the follow-up research [38][39][40]. Topoisomerase was a critical type of enzyme for overcoming the problem of chromosome topology that arose during DNA replication, transcription, recombination, and mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitin-proteasome system regulates transcription via polyubiquitination that leads to removal of DNA-associated proteins ( 69 , 70 ). Cul1, an Ank13 interacting partner and SCF component, is abundant in the nucleus and associates with 23% of all DNA-associated protein degradation sites ( 69 ). In addition to commandeering the SCF complex in the cytoplasm, Ank13 does so in the nucleus as its major means of modulating gene expression.…”
Section: Discussionmentioning
confidence: 99%